Clinical Outcomes in Patients with Cardiac Lupus: A Retrospective Study - K Maria Koshy; Tarun George; Sohini Das; J V Punitha; Sudha Jasmine Rajan; Bijesh Yadav; Thambu David Sudarsanam; Vijay Prakash Turaka (Indian Journal of Rheumatology)
Objectives: Systemic lupus erythematosus (SLE) is an autoimmune disease that can affect every organ system. The study aimed to analyze the clinical manifestations, laboratory findings, antibody associations, and clinical outcomes of patients with cardiac lupus. Materials and Methods: Biomedical records of patients admitted during 2014–2017 who had a diagnosis of SLE were reviewed. Using predetermined inclusion criteria patients with cardiac lupus were identified. Disease manifestations, antibody associations, and clinical outcomes were studied. The Cox proportional hazards model was used to study factors associated with mortality. Results: Over a 3-year period, a total of 372 were admitted with a diagnosis of SLE, out of which 59 patients with cardiac lupus were identified. The patients were predominantly female (86.4%), fever and breathlessness were most common symptoms and the median SLE disease activity index score was 18. Myocardial disease (66.1%), pericardial disease (30.5%), and pulmonary artery hypertension (23.7%) were the most common cardiac manifestations. The mean ejection fraction was 46% ±11.4% with left ventricular systolic dysfunction present in 65.5% (n = 36). The inpatient mortality rate was 22% (n = 13). An elevated serum creatinine, elevated creatine Kinase–muscle/brain, neutrophilic leukocytosis, left ventricular systolic dysfunction, noninitiation of hydroxychloroquine, and the presence of neuropsychiatric lupus predicted mortality. On follow-up, 12 of the 13 echocardiograms demonstrated normal findings. Conclusion: Cardiac disease affects a significant proportion of patients with lupus. A high mortality rate as evident from this study, highlights the importance of recognizing the cardiac complications of SLE. Clinicians should diligently search for the same, as early interventions could reduce mortality and morbidity.